Pertanggungjawaban Pidana Pelaku Turut Serta Dalam Tindak Pidana Korupsi Penerimaan Suap Oleh Hakim - Oktafianto, Wahyu Dwi; Kristiawanto, Kristiawanto; Nainggolan, Marsudin (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
The rise of criminal acts of corruption, especially in the world of justice, will certainly seriously harm justice for society. The judiciary, which should be a place for people to seek justice, has now become a transactional institution by a handful of certain individuals and the judicial mafia. The criminal act of corruption in accepting bribes by judges of course does not only involve the judge himself, of course it will involve other parties, namely those closest to him or those he trusts who both work as judges or civil servants and can even involve private parties. Therefore, these other parties must also be held criminally responsible for their actions, namely as participating perpetrators (medeplegen) by applying the doctrine of deelneming based on Article 55 paragraph (1) 1 of the Criminal Code (KUHP). This research is normative juridical research with a statutory approach, a case approach, a historical approach and a comparative approach and uses the theory of criminal liability and the theory of deelneming. In its development, there have been many different views for judges in deciding cases of participating perpetrators who do not have certain qualities as stated in the article in which they are charged. In the teaching of deelneming, what needs to be seen and proven is the role and action (actus reus and mens rea) of the participating actor, not looking at who or the quality of the participating actor. The expansion of inclusion or participation should be based on the concept of knowledge and agreeing which is not seen simply as evil thoughts or evil intentions (mens rea) of the perpetrator but is placed directly on the role and actions (actus reus) as a new form of deelneming or participation.